Effects of Added Calcium Carbonate on Weanling Pig Growth Performance - Alan J. Warner; Joel M DeRouchey; Mike D. Tokach; Jason C. Woodworth; Robert D. Goodband; Jordan T. Gebhardt (Kansas Agricultural Experiment Station Research Reports, 2021)
A total of 695 barrows (DNA Line 200 × 400; initially 12.9 lb) were used in two groups in a 28-d study to evaluate the effects of added dietary calcium carbonate on phase 1 nursery pig growth performance and fecal dry matter. Upon arrival to the nursery research facility, pigs were randomly assigned to pens (5 pigs per pen) and pens were allotted to 1 of 5 dietary treatments with 27 or 28 pens per treatment. Dietary treatments were formulated to provide 0, 0.45, 0.90, 1.35, and 1.80% calcium carbonate added at the expense of corn. Analyzed Ca for treatment diets were 0.61, 0.80, 0.99, 1.15, and 1.37%, respectively. Standardized total tract P concentration was formulated to 0.58% in all diets. Diets were fed in two phases with treatment diets fed from weaning (d 0) to d 14 and a common phase 2 diet fed from d 14 to 28. Treatment diets were fed in both meal (group 1) and pellet (group 2) form. There was no evidence for treatment × group interaction observed, so data from both groups were combined. From d 0 to 14 (treatment period), ADG, d 14 BW, and F/G worsened (linear,P= 0.010) as calcium carbonate increased. There was no evidence for difference for ADFI (P>0.10). From d 14 to 28 (common period) and for the overall experiment (d 0 to 28), there was no evidence (P>0.10) for differences observed for any growth performance criteria. For fecal dry matter, there was a tendency (quadratic,P= 0.091) with the highest and lowest calcium carbonate diets having the highest dry matter. In summary, increasing dietary calcium carbonate from 0 to 1.80% decreases ADG and worsens feed efficiency in phase 1 nursery diets. Despite the linear response, the largest decrease was observed when calcium carbonate increased from 0.45 to 0.90% with no difference in performance thereafter. These data suggest that lower levels of calcium carbonate can be used than are typically added to phase 1 diets.
Keywords: acid binding capacity; calcium carbonate; gain; feed efficiency; nursery pig